1991
DOI: 10.1093/infdis/163.3.656
|View full text |Cite
|
Sign up to set email alerts
|

Antiborrelial Activity of Serum from Rats Injected with the Lyme Disease Spirochete

Abstract: The functional properties of humoral factors generated in rats immunized against Borrelia burgdorferi were investigated. After Lewis strain rats were injected intraperitoneally with live B. burgdorferi or in the footpad with dead borreliae incorporated in complete Freund's adjuvant, they produced high-titered antisera. At a dilution of less than or equal to 1:10, sera from immunized or infected rats but not control sera inhibited growth of B. burgdorferi in vitro. Neutralization of growth of three different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 10 publications
3
20
0
Order By: Relevance
“…Results showed that heat inactivation of complement decreased the degree of lysis observed in some samples but had no effect on aggregation, bleb formation, loss of motility, or overall score. Furthermore, inactivation of complement did not eliminate antiborrelial activity of any sample, a finding consistent with previous reports of non-complement-dependent borreliacidal antibodies (2,10,12,13).Serum samples obtained from 20 recipients of the recombinant OspA-based vaccine were tested by in vitro incubation with viable spirochetes (4). Specimens included serum samples obtained at time zero (before any doses of vaccine were given) (baseline values), 30 days following the first dose of vaccine, 30 days following the second dose of vaccine, 6 months following the second dose, 1 year following the first dose, and 30 days following the third dose of the vaccine.…”
supporting
confidence: 85%
“…Results showed that heat inactivation of complement decreased the degree of lysis observed in some samples but had no effect on aggregation, bleb formation, loss of motility, or overall score. Furthermore, inactivation of complement did not eliminate antiborrelial activity of any sample, a finding consistent with previous reports of non-complement-dependent borreliacidal antibodies (2,10,12,13).Serum samples obtained from 20 recipients of the recombinant OspA-based vaccine were tested by in vitro incubation with viable spirochetes (4). Specimens included serum samples obtained at time zero (before any doses of vaccine were given) (baseline values), 30 days following the first dose of vaccine, 30 days following the second dose of vaccine, 6 months following the second dose, 1 year following the first dose, and 30 days following the third dose of the vaccine.…”
supporting
confidence: 85%
“…After disruption of the outer Bacteriostatic and bactericidal activities of anti-rBmpA antibody. If the BmpA protein was located on the outer cell membrane of B. burgdorferi, antibody could be deposited on the bacterial cell surface and trigger biological phenomena related to this deposition, including activation of complement, bacteriostasis, and bacteriolysis (17,30,35,39). B. burgdorferi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, our laboratory has previously reported results that have demonstrated the in vitro borreliacidal activities of penicillin-type and various cephalosporin-type antibiotics (6,7), as well as of sera from Lyme disease patients (8). This report describes a follow-up study of the effects of a novel antibiotic, evernimicin, on the growth of a large number of North American isolates of Borrelia burgdorferi.…”
mentioning
confidence: 98%
“…Microculture techniques have recently been described and are especially useful for assessment of the growth of the Lyme disease spirochete in the presence of certain potentially inhibitory substances such as immune sera and antibiotics (1,(4)(5)(6)(7)(8)(9). In this regard, our laboratory has previously reported results that have demonstrated the in vitro borreliacidal activities of penicillin-type and various cephalosporin-type antibiotics (6,7), as well as of sera from Lyme disease patients (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation